“Himalayan Bridge”: A New Unstable Suspended Bridge to Investigate Rodents' Venturesome Behavior - Festucci, Fabiana; Buccheri, Clelia; Parvopassu, Anna; Oggiano, Maurizio; Bortolato, Marco; Laviola, Giovanni; Curcio, Giuseppe; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2021)
Risk-taking behavior is necessary for survival in all mammalian species while, on the opposite, the excessive avoidance of potential dangers is at the basis of anxiety disorders. The dopamine system and its key regulator, DAT, are known modulators of risk seeking/avoidance. To study risk proneness vs anxiety in laboratory rodents, their innate fear of heights is often used: instead of the classic elevated plus-maze, we were inspired by a suspended wire bridge used with mice, adapting it to the rats’ size and modifying the protocol: we aimed to investigate the venturesome behavior together with perception of own distance from end point and of bridge stability. Apparatus is composed of a starting point and an end point elevated scaffolds, connected by bridges of different lengths and stability. Such apparatus made rats walk one meter above the floor, which was covered with foam rubber: subjects had to cross the bridge to reach food. We measured crossings, pawslips, turnabouts, and latencies. Furthermore, given the link between risky behavior and adolescence, we investigated the influence, over the adolescent development of risk-taking behavior excited the homecage mate. Thus 24 wild-type (WT) subjects were divided into three different housing groups: WT adult rats grown up with an adult WT rats; control WT adolescent rats (grown up with WT adolescents), who showed a proclivity to risk; WT rats grown up with an adult truncated-DAT rat, who showed an anxious-like behavior. This apparatus seems useful to investigate risk perception and seeking in rodents: its use can be extended to behavioral phenotyping of some psychiatric disorders, and cognitive dysfunctions, in rat models.